Let the length of the shorter leg of the triangle be x cm So, the length of the longer leg is x+ 2 cm the length of the hypotenuse = x+4 cm Pythagorean theorem states that "The square of the hypotenuse is equal to the sum of squares of the other two sides." Therefore, (x+4)^2 = x^2 + (x+2)^2 x^2 + 8x + 16 = x^2 + x^2 +4x + 4 x^2 - 4x - 12=0 Let's factorize using splitting the middle term method, x^2 - 6x + 2x - 12 =0 x(x-6) +2(x-6)=0 (x+2)(x-6)=0 x=-2 or x=6 As we have taken x as the length, it cannot be negative. Therefore x= 6cm Longer side = x+2 =6+2 = 8 cm Hypotenuse = x + 4 = 6+4=10 cm The sides are, 6cm, 8cm and 10 cm.